Presenting the Joint Educational Project of the Russian Federal Center of Forensic Science of the Ministry of Justice of the Russian Federation and the Peoples' Friendship University of Russia - E. V. Chesnokova (Теория и практика судебной экспертизы)
The article discusses the creation and functioning of the educational project based on the partnership between the Russian Federal Center of Forensic Science of the Ministry of Justice of the Russian Federation (engaged in forensic practice, scientific research, and methodology development) and the Peoples' Friendship University of Russia (engaged in education and training). The author examines the problems of modern professional training in forensic disciplines within the system of higher education. The system of the joint PFUR– RFCFS educational project is described and constituent levels of training are characterized. Pathways for future development of the project are offered.